Utilization of Folklore in Optimizing Ngarai Sianok Tourist Destination in Bukittinggi West Sumatra Indonesia: al-Istifādah min al-Turāś al-Syu’bī fī Taḥsīni Wijhati Ngarai Sianok Tourist bi Bukittinggi Sumaṭrah Garbiyyah Indunīsiyyā - Pratiwi, Dyani Prades; Firmansyah, Okta; Hawa, Andina Meutia; Gayatri, Satya; Muhajir, Ahmad (Study Program of Arabic Language Teaching, 2023)
This study aims to provide recommendations for folklore branding strategies for the Ngarai Sianok tourist destination in Bukittinggi as an effort to restore tourism in Bukttinggi. The research method used is descriptive qualitative by conducting a literature review of folklore and data relating to the Ngarai Sianok tourist destination as the primary data. Supporting data is in the form of data obtained from scientific articles and popular articles, as well as interviews with relevant subjects, such as the Tourism Office, Tour and Travel Agents, and tour guides. Data analysis uses the storynomics theory by Robert Mcee and Thomas Gerace by focusing on stories as a strategy to improve the economy, in this case through tourist destinations. The results of this study are that folklore has a positive influence to be developed as a branding strategy for Ngarai Sianok tourist destinations. Folklore can become narratives of tour guides and narratives of tourism promotion at this destination. In addition, folklore can be an inspiration for making souvenirs that can improve the community's creative economy around tourist destinations. Utilizing folklore can enhance the reputation of the Ngarai Sianok and become a medium for character education in a fun way. The dissemination of the Legend of Ngarai Sianok can also be an effort to preserve the folklore of Bukittinggi and support the realization of Indonesian tourism based on local wisdom.